Structural disorder and induced folding within two cereal, ABA stress and ripening (ASR) proteins. Issue 1 (December 2017) - Hamdi, Karama; Salladini, Edoardo; O'Brien, Darragh; Brier, Sébastien; Chenal, Alexandre; Yacoubi, Ines; Longhi, Sonia
Abstract A bscisic acid (ABA), s tress andr ipening (ASR) proteins are plant-specific proteins involved in plant response to multiple abiotic stresses. We previously isolated the ASR genes and cDNAs from durum wheat (TtASR1) and barley (HvASR1). Here, we show that HvASR1 and TtASR1 are consistently predicted to be disordered and further confirm this experimentally. Addition of glycerol, which mimics dehydration, triggers a gain of structure in both proteins. Limited proteolysis showed that they are highly sensitive to protease degradation. Addition of 2, 2, 2-trifluoroethanol (TFE) however, results in a decreased susceptibility to proteolysis that is paralleled by a gain of structure. Mass spectrometry analyses (MS) led to the identification of a protein fragment resistant to proteolysis. Addition of zinc also induces a gain of structure and Hydrogen/Deuterium eXchange-Mass Spectrometry (HDX-MS) allowed identification of the region involved in the disorder-to-order transition. This study is the first reported experimental characterization of HvASR1 and TtASR1 proteins, and paves the way for future studies aimed at unveiling the functional impact of the structural transitions that these proteins undergo in the presence of zinc and at achieving atomic-resolution conformational ensemble description of these two plant intrinsically disordered proteins (IDPs).